Pengaruh ukuran perusahaan, profitabilitas, kebijakan utang, likuiditas, dan struktur modal terhadap nilai perusahaan - Epi Meyorga; Pujo Gunarso; Any Rustia Dewi (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2024)
This research aims to analyze the influence of size, profitability, debt policy and capital structure on company value. The population in this study was 55 companies, the sampling technique used purposive sampling, resulting in a total sample of 13 companies during the 2020 - 2022 period. The data analysis technique used multiple regression analysis. The results of the analysis show that company size has a significant effect on company value. Profitability, debt policy, liquidity and capital structure have no effect on company value.